SARS-CoV-2 Spike Protein Is Capable of Inducing Cell–Cell Fusions Independent from Its Receptor ACE2 and This Activity Can Be Impaired by Furin Inhibitors or a Subset of Monoclonal Antibodies - Reuter, Nina; CHEN, XIAOHAN; Kropff, Barbara; Peter, Antonia Sophia; Britt, William J.; Mach, Michael; Überla, Klaus; Thomas, Marco (Viruses, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which was responsible for the COVID-19 pandemic, efficiently spreads cell-to-cell through mechanisms facilitated by its membrane glycoprotein spike. We established a dual split protein (DSP) assay based on the complementation of GFP and luciferase to quantify the fusogenic activity of the SARS-CoV-2 spike protein. We provide several lines of evidence that the spike protein of SARS-CoV-2, but not SARS-CoV-1, induced cell–cell fusion even in the absence of its receptor, angiotensin-converting enzyme 2 (ACE2). This poorly described ACE2-independent cell fusion activity of the spike protein was strictly dependent on the proteasomal cleavage of the spike by furin while TMPRSS2 was dispensable. Previous and current variants of concern (VOCs) differed significantly in their fusogenicity. The Delta spike was extremely potent compared to Alpha, Beta, Gamma and Kappa, while the Omicron spike was almost devoid of receptor-independent fusion activity. Nonetheless, for all analyzed variants, cell fusion was dependent on furin cleavage and could be pharmacologically inhibited with CMK. Mapping studies revealed that amino acids 652-1273 conferred the ACE2-independent fusion activity of the spike. Unexpectedly, residues proximal to the furin cleavage site were not of major relevance, whereas residue 655 critically regulated fusion. Finally, we found that the spike’s fusion activity in the absence of ACE2 could be inhibited by antibodies directed against its N-terminal domain (NTD) but not by antibodies targeting its receptor-binding domain (RBD). In conclusion, our BSL-1-compatible DSP assay allowed us to screen for inhibitors or antibodies that interfere with the spike’s fusogenic activity and may therefore contribute to both rational vaccine design and development of novel treatment options against SARS-CoV-2.
CRIS-Team Scopus Importer:2023-08-11
Keywords: ACE2; antibodies; cell–cell fusion; furin; glycoprotein; inhibitors; neutralization; receptor-independent; screening; severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); spike; therapy; variants of concern (VOCs)